Nickel-based catalyst for improving methane activation capability and application of nickel-based catalyst in pressurized CH4-CO2 reforming synthesis gas
By introducing ZrO2 additives into the nickel-based catalyst to form a Ni-ZrO2 interface, the problem of catalysts prone to carbon deactivation in the pressurized CH4-CO2 reforming reaction is solved, and the high activity and good stability of the catalyst are achieved.
Patent Information
- Application Number
- CN202411535032.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The existing nickel-based catalysts are prone to carbon accumulation and deactivation during the pressurized CH4-CO2 reforming reaction, resulting in a decrease in the stability and activity of the catalyst.
Using Ni-ZrO2-SiO2 catalyst, the active metal Ni and the additive ZrO2 are uniformly dispersed, and the Ni-ZrO2 interface is formed, which significantly inhibits the sintering of metal Ni particles and improves the catalyst's anti-carbon accumulation performance.
Under pressurized conditions, the methane conversion rate of the catalyst reached about 58%, which was close to the thermodynamic equilibrium conversion rate. After 75 hours of operation, it only showed a weak attenuation, which significantly improved the stability and activity of the catalyst.
Smart Images

Figure CN119406411A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fossil energy chemical industry, and specifically relates to a nickel-based catalyst for improving the activation ability of methane and its application in pressurized CH4-CO2 reforming to produce synthesis gas. Background Art
[0002] Under the background of "dual carbon", the efficient use of CO2 resources to produce high value-added chemical products has become an important direction for the utilization of CO2 resources. As the main component of natural gas, the deep utilization of CH4 is mainly achieved through the indirect method of preparing chemical products from syngas. In industry, syngas is mainly prepared by steam reforming, but the production process consumes huge energy. In contrast, the CH4-CO2 reforming reaction (CRM) can convert CO2 and CH4 into syngas, which helps to reduce greenhouse gas emissions; and the resulting syngas H2 / CO≤1 can be used as a raw material for the synthesis of carbonyl and oxygen-containing compounds. Therefore, CRM has become a promising indirect conversion and utilization technology for CO2 and CH4. Given that natural gas is stored and transported under pressure, and chemical production processes such as Fischer-Tropsch synthesis and methanol synthesis that use syngas as raw materials also generally use pressurized operations, from the perspective of overall energy efficiency and investment cost, pressurized CRM can reduce the size of the reactor and save the subsequent syngas pressurization operation, making it more reasonable and efficient.
[0003] For CRM, nickel-based catalysts have the advantages of high activity, cheap components and wide sources, but they also have the fatal weakness of easy carbon deposition and deactivation. A comprehensive analysis of existing catalyst research shows that the measures to improve the anti-coking performance of catalysts around the CRM active center Ni mainly include: ① introducing oxide additives (La2O3, CeO2, ZrO2, etc.); ② introducing transition metals (Fe, Cu, Co) or precious metals (Pt, Ir, etc.); ③ changing the carrier type (SiO2, Al2O3, CeO2, etc.); ④ regulating Ni dispersion or metal-carrier interaction. For atmospheric pressure CRM, the anti-coking performance of the catalysts improved by the above measures has been significantly improved. However, for pressurized CRM, considering that the increase in pressure has a great influence on the catalytic mechanism, kinetics, and carbon deposition behavior of CRM, the catalysts improved by the above measures may experience rapid carbon deposition and deactivation under pressurized conditions. Therefore, it is necessary to develop pressurized CRM nickel-based catalysts and preparation methods in a targeted manner. Summary of the invention
[0004] The purpose of the present invention is to provide a nickel-based catalyst for improving the activation ability of methane. The catalyst has a simple preparation method and easily controllable reaction conditions. It has high reaction activity, excellent anti-carbon deposition performance and good stability for pressurized CH4-CO2 reforming to produce synthesis gas.
[0005] In order to achieve the above-mentioned purpose, the active ingredient of the catalyst used in the present invention is Ni, the auxiliary ingredient is ZrO2, the carrier is SiO2, and the general formula of the catalyst is xNi-yZrO2-SiO2, wherein x is the mass percentage of Ni in the catalyst, y is the mass percentage of ZrO2 in the catalyst, the value of x is 8% to 15%, and the value of y is 2.5% to 20%; the preparation method of the catalyst is: according to the catalyst composition, nickel salt and zirconium salt are dissolved in deionized water, the obtained solution is added dropwise to silica sol under stirring, and a β-cyclodextrin aqueous solution is added and stirred for 1.5 to 3 hours; then the temperature is raised to 60 to 80°C and stirred until dry, and the mixture is transferred to a blast drying oven at a constant temperature of 70 to 120°C and dried for 8 to 12 hours, and then transferred to a muffle furnace and calcined at a constant temperature of 700 to 800°C for 4 to 8 hours, naturally cooled to room temperature, ground, tableted and sieved to obtain 40 to 60 mesh particles, i.e., the catalyst.
[0006] In the above catalyst, preferably, the value of x is 10%, and the value of y is 5% to 15%.
[0007] In the preparation method of the above catalyst, the nickel salt is nickel nitrate hexahydrate, and the zirconium salt is zirconium nitrate pentahydrate or zirconium oxynitrate (IV) hydrate.
[0008] In the preparation method of the above catalyst, the added amount of the β-cyclodextrin is preferably 0.05 to 0.25 times the total molar amount of metal ions in the nickel salt and the zirconium salt.
[0009] In the above-mentioned method for preparing the catalyst, it is preferred to dry the catalyst in a forced air drying oven at a constant temperature of 100 to 110° C. for 8 to 12 hours.
[0010] In the above-mentioned preparation method of the catalyst, it is preferred to calcine at a constant temperature of 750° C. in a muffle furnace for 6 hours.
[0011] The present invention also provides an application of the nickel-based catalyst in pressurized CH4-CO2 reforming to produce synthesis gas, and the specific method is: the nickel-based catalyst is loaded into a fixed bed reactor and subjected to H2 high-temperature reduction treatment, and a CH4 and CO2 mixed gas is introduced at a temperature of 700-800°C, a pressure of 0.1-1.0MPa, a total gas flow rate of 80-150mL / min, and a space velocity of 48000-90000mL@g -1 ·h -1 The synthesis gas is obtained by reforming reaction.
[0012] In the above application, it is preferred that the H2 flow rate of the H2 high temperature reduction treatment is 40-80 mL / min, the reduction temperature is 700-800° C., and the reduction time is 1-2 h.
[0013] In the above application, the CH4 / CO2 molar ratio in the mixed gas is preferably 1 to 2, the temperature is 700 to 800°C, the pressure is 0.5 MPa, the total gas flow rate is 100 mL / min, and the space velocity is 60000 mL@g -1 @h -1 The synthesis gas is obtained by reforming reaction.
[0014] The beneficial effects of the present invention are as follows:
[0015] The active metal Ni and the auxiliary agent ZrO2 in the catalyst of the present invention are uniformly dispersed in the carrier SiO2 and form a Ni-ZrO2 interface. The highly dispersed ZrO2 significantly inhibits the sintering of metal Ni particles and regulates the activation ability of metal Ni to CH4. The raw materials used in the preparation method of the catalyst of the present invention are cheap, the preparation conditions are easy to control, the process is simple, and the obtained catalyst is easy to reproduce. The catalyst of the present invention is used for the pressurized CH4-CO2 reforming reaction to produce synthesis gas, and the methane conversion rate can reach up to about 58% (750°C, 0.5MPa), which is close to the thermodynamic equilibrium conversion rate under the reaction conditions, and only a slight attenuation occurs after running for 75 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is the XRD spectra of the 10Ni-yZrO2-SiO2 catalysts prepared in Examples 1 to 5 and the 10Ni-SiO2 catalyst prepared in Comparative Example 1.
[0017] Figure 2 It is the XRD spectra of the 10Ni-yZrO2-SiO2 catalysts prepared in Examples 1 to 5 and the 10Ni-SiO2 catalyst prepared in Comparative Example 1 after reduction in H2 atmosphere.
[0018] Figure 3 This is a high-resolution transmission electron micrograph of the 10Ni-15ZrO2-SiO2 catalyst (after reduction) prepared in Example 5.
[0019] Figure 4 This is a spherical aberration corrected transmission electron microscopy image of the 10Ni-15ZrO2-SiO2 catalyst (after reduction) prepared in Example 5.
[0020] Figure 5 It is a CH4-programmed temperature surface reaction diagram of the 10Ni-yZrO2-SiO2 catalyst prepared in Examples 1, 3, and 5 and the 10Ni-SiO2 catalyst prepared in Comparative Example 1.
[0021] Figure 6 It is a trend chart of the average metal Ni particle size of the 10Ni-yZrO2-SiO2 catalysts prepared in Examples 1, 3, and 5 and the 10Ni-SiO2 catalyst prepared in Comparative Example 1 as a function of reaction time. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0023] Example 1
[0024] According to the composition of the catalyst 10% Ni-2.5% ZrO2-SiO2, 0.8258 g (2.84 mmol) of nickel nitrate hexahydrate and 0.1810 g (0.42 mmol) of zirconium nitrate pentahydrate were dissolved in 40 mL of deionized water to obtain a metal salt solution; 0.7403 g (0.65 mmol) of β-cyclodextrin was dissolved in 100 mL of deionized water to obtain a β-cyclodextrin aqueous solution; the above metal salt aqueous solution was added dropwise to 5.0 g silica sol and stirred at 400 rpm, then the above-mentioned β-cyclodextrin aqueous solution was added and the rotation speed was adjusted to 500 rpm and stirring was continued for 2 hours; then the temperature was raised to 70°C and stirred until dry, transferred to a blast drying oven and dried at 100°C for 12 hours, and then transferred to a muffle furnace and calcined at 750°C for 6 hours; naturally cooled to room temperature, ground, pressed into tablets and sieved to obtain 40-60 mesh particles, which were prepared into a catalyst, recorded as 10Ni-2.5ZrO2-SiO2.
[0025] Comparative Example 1
[0026] In Example 1, zirconium nitrate pentahydrate was not added and the amount of β-cyclodextrin was reduced to 0.6446 g (0.57 mmol). The other preparation steps were the same as in Example 1 to prepare a catalyst, which was recorded as 10Ni-SiO2.
[0027] Example 2
[0028] According to the composition of the catalyst 10% Ni-5% ZrO2-SiO2, 0.8258 g (2.84 mmol) of nickel nitrate hexahydrate and 0.3715 g (0.87 mmol) of zirconium nitrate pentahydrate were dissolved in 40 mL of deionized water to obtain a metal salt solution; 0.8411 g (0.74 mmol) of β-cyclodextrin was dissolved in 100 mL of deionized water to obtain a β-cyclodextrin aqueous solution; the other steps were the same as in Example 1 to prepare a catalyst, recorded as 10Ni-5ZrO2-SiO2.
[0029] Example 3
[0030] According to the composition of the catalyst 10% Ni-7.5% ZrO2-SiO2, 0.8258 g (2.84 mmol) of nickel nitrate hexahydrate and 0.5724 g (1.33 mmol) of zirconium nitrate pentahydrate were dissolved in 40 mL of deionized water to obtain a metal salt solution; 0.9473 g (0.83 mmol) of β-cyclodextrin was dissolved in 100 mL of deionized water to obtain a β-cyclodextrin aqueous solution; the other steps were the same as in Example 1 to prepare a catalyst, recorded as 10Ni-7.5ZrO2-SiO2.
[0031] Example 4
[0032] According to the composition of the catalyst 10% Ni-10% ZrO2-SiO2, 0.8258 g (2.84 mmol) of nickel nitrate hexahydrate and 0.7844 g (1.83 mmol) of zirconium nitrate pentahydrate were dissolved in 40 mL of deionized water to obtain a metal salt solution; 1.0594 g (0.93 mmol) of β-cyclodextrin was dissolved in 100 mL of deionized water to obtain a β-cyclodextrin aqueous solution; the other steps were the same as in Example 1 to prepare a catalyst, recorded as 10Ni-10ZrO2-SiO2.
[0033] Example 5
[0034] According to the composition of the catalyst 10% Ni-15% ZrO2-SiO2, 0.8258 g (2.84 mmol) of nickel nitrate hexahydrate and 1.2458 g (2.90 mmol) of zirconium nitrate pentahydrate were dissolved in 40 mL of deionized water to obtain a metal salt solution; 1.3033 g (1.15 mmol) of β-cyclodextrin was dissolved in 100 mL of deionized water to obtain a β-cyclodextrin aqueous solution; the other steps were the same as in Example 1 to prepare a catalyst, recorded as 10Ni-15ZrO2-SiO2.
[0035] The fresh catalysts prepared in Examples 1 to 5 and Comparative Example 1 were characterized using a D8 Advance X-ray powder diffractometer. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the 10Ni-yZrO2-SiO2 catalysts prepared in Examples 1 to 5 all have good NiO and ZrO2 dispersibility. The catalysts were reduced in pure H2 at a flow rate of 50 mL / min at a heating rate of 15°C / min from room temperature to 750°C for 2 h, and then characterized by XRD. The results are as follows: Figure 2 As shown. Figure 2It can be seen that the 10Ni-yZrO2-SiO2 catalysts prepared in Examples 1 to 5 all showed weak characteristic diffraction peaks of metallic Ni after H2 reduction treatment, indicating that metallic Ni has good dispersibility, and ZrO2 still maintains good dispersibility after H2 reduction treatment.
[0036] The reduction catalyst prepared in Example 5 was characterized using a JEM 2100F transmission electron microscope and a Titan Themis G2 60-300 spherical aberration corrected electron microscope. Figures 3-4 As shown. Figures 3-4 It can be seen that after the reduction treatment of the catalyst prepared in Example 5, an obvious interface is formed between the active metal Ni particles and the additive ZrO2.
[0037] The 10Ni-yZrO2-SiO2 catalysts prepared in Examples 1, 3, and 5 and the 10Ni-SiO2 catalyst prepared in Comparative Example 1 were subjected to a CH4-programmed temperature surface reaction experiment using an AutochemⅡ2950 chemical adsorption instrument coupled with a QIC-20 mass spectrometer. The results are shown in FIG. Figure 5 As shown. Figure 5 It can be seen that the CH4 activation temperature of the Ni-yZrO2-SiO2 catalyst prepared in Examples 1, 3, and 5 is 151 to 163°C lower than that of the 10Ni-SiO2 catalyst prepared in Comparative Example 1, indicating that the introduction of the ZrO2 additive can significantly enhance the activation ability of metal Ni for CH4; in addition, as the ZrO2 loading increases, the CH4 activation temperature of the catalyst shows a gradual downward trend (365°C→356°C→353°C), indicating that changing the ZrO2 loading can regulate the activation ability of metal Ni for CH4.
[0038] Example 6
[0039] The application of the catalysts in Examples 1 to 5 in pressurized CH4-CO2 reforming to produce synthesis gas is as follows:
[0040] 0.1g of catalyst was mixed with 1.0g of quartz sand and placed in the center of the fixed bed reactor. Pure H2 was introduced at a flow rate of 50mL / min under normal pressure. The temperature was raised from room temperature to 750℃ at a rate of 15℃ / min and reduced for 2h. After the reduction, pure N2 was switched to be purged at a flow rate of 50mL / min, and the back pressure valve was adjusted to raise the reactor pressure to 0.5MPa. After the reactor pressure stabilized, the reaction was started by switching to a mixed gas with a CH4 / CO2 molar ratio of 1 at a flow rate of 100mL / min. At a pressure of 0.5MPa, a reaction temperature of 750℃, and a space velocity of 60000mL@g -1 ·h -1The reforming reaction was carried out for 75 hours under the conditions of , and the gas after the reaction was detected and analyzed online by Pano A91 PLUS gas chromatograph (the chromatographic column was HQ column) after water removal. The experimental results are shown in Table 1. At the same time, a comparative experiment was carried out with the 10Ni-SiO2 catalyst prepared in Comparative Example 1.
[0041] Table 1 Effect of ZrO2 content on CH4-CO2 reforming performance of catalyst
[0042]
[0043]
[0044] As shown in Table 1, the 10Ni-yZrO2-SiO2 catalysts prepared in Examples 1 to 5 of the present invention and the 10Ni-SiO2 catalyst prepared in Comparative Example 1 both exhibited high CH4-CO2 reforming reaction activity, with initial conversion rates of CH4 and CO2 being 43% to 58% and 61% to 74%, respectively. However, after 75 hours of reaction, the CH4 and CO2 conversion rates of the 10Ni-SiO2 catalyst (Comparative Example 1) dropped from 42.8% and 61.2% to 24.9% and 43.4%, respectively. In contrast, after 75 hours of reaction, the CH4 and CO2 conversion rates of the 10Ni-2.5ZrO2-SiO2 catalyst dropped from 58.6% and 73.6% to 49.7% and 65.5%, respectively, but were still better than those of the 10Ni-SiO2 catalyst. The 10Ni-5ZrO2-SiO2 catalyst, 10Ni-7.5ZrO2-SiO2 catalyst, 10Ni-10ZrO2-SiO2 catalyst and 10Ni-15ZrO2-SiO2 catalyst showed excellent catalytic stability, and their CH4 and CO2 conversion rates decreased by 1.9% to 2.8% and 1% to 2.5%, respectively.
[0045] The average metal Ni particle size of the 10Ni-yZrO2-SiO2 catalysts prepared in Examples 1, 3, and 5 and the 10Ni-SiO2 catalyst prepared in Comparative Example 1 after different reaction times was calculated, and the trend of the average metal Ni particle size changing with time was obtained. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that as the reaction proceeds, the average Ni particle size of all catalysts shows an increasing trend, but the increase in the average Ni particle size of the 10Ni-yZrO2-SiO2 catalyst prepared in Examples 1, 3, and 5 is much lower than that of the 10Ni-SiO2 catalyst prepared in Comparative Example 1, indicating that the ZrO2 additive significantly inhibits the sintering of metal Ni particles.
Claims
1. A nickel-based catalyst for improving methane activation ability, characterized in that: The active component of the catalyst is Ni, the auxiliary component is ZrO2, the carrier is SiO2, and the general formula of the catalyst is xNi-yZrO2-SiO2, wherein x is the mass percentage of Ni in the catalyst, y is the mass percentage of ZrO2 in the catalyst, the value of x is 8% to 15%, and the value of y is 2.5% to 20%; The preparation method of the catalyst is as follows: according to the catalyst composition, nickel salt and zirconium salt are dissolved in deionized water, the obtained solution is dripped into silica sol under stirring, and a β-cyclodextrin aqueous solution is added and stirred for 1.5 to 3 hours; then the temperature is raised to 60 to 80° C. and stirred until dry, and the mixture is transferred into a blast drying oven and dried at a constant temperature of 70 to 120° C. for 8 to 12 hours, and then transferred to a muffle furnace and calcined at a constant temperature of 700 to 800° C. for 4 to 8 hours, and naturally cooled to room temperature, and ground, tableted and sieved to obtain 40 to 60 mesh particles, namely the catalyst.
2. The nickel-based catalyst for improving methane activation ability according to claim 1, characterized in that: The value of x is 10%, and the value of y is 5% to 15%.
3. The nickel-based catalyst for improving methane activation ability according to claim 1, characterized in that: The nickel salt is nickel nitrate hexahydrate, and the zirconium salt is zirconium nitrate pentahydrate or zirconium oxynitrate (IV) hydrate.
4. The nickel-based catalyst for improving methane activation ability according to claim 1, characterized in that: The added amount of the beta-cyclodextrin is 0.05 to 0.25 times the total molar amount of metal ions in the nickel salt and the zirconium salt.
5. The nickel-based catalyst for improving methane activation ability according to claim 1, characterized in that: Dry in a blast drying oven at a constant temperature of 100-110°C for 8-12 hours.
6. The nickel-based catalyst for improving methane activation ability according to claim 1, characterized in that: The resulting composites were calcined at 750°C in a muffle furnace for 6 hours.
7. Use of the nickel-based catalyst according to any one of claims 1 to 6 in pressurized CH4-CO2 reforming to produce synthesis gas.
8. Use of the nickel-based catalyst according to claim 7 in pressurized CH4-CO2 reforming to produce synthesis gas, characterized in that: The nickel-based catalyst is loaded into a fixed bed reactor and treated with H2 high-temperature reduction, and then a mixed gas of CH4 and CO2 is introduced at a temperature of 700-800°C, a pressure of 0.1-1.0 MPa, a total gas flow rate of 80-150 mL / min, and a space velocity of 48000-90000 mL·g -1 ·h -1 The synthesis gas is obtained by reforming reaction.
9. Use of the nickel-based catalyst according to claim 8 in pressurized CH4-CO2 reforming to produce synthesis gas, characterized in that: The H2 high temperature reduction treatment has a H2 flow rate of 40 to 80 mL / min, a reduction temperature of 700 to 800° C., and a reduction time of 1 to 2 h.
10. Use of the nickel-based catalyst according to claim 8 in pressurized CH4-CO2 reforming to produce synthesis gas, characterized in that: The CH4 / CO2 molar ratio in the mixed gas is 1-2, the temperature is 700-800°C, the pressure is 0.5 MPa, the total gas flow rate is 100 mL / min, and the space velocity is 60000 mL·g -1 ·h -1 The synthesis gas is obtained by reforming reaction.